2022
DOI: 10.1021/jacs.2c08585
|View full text |Cite
|
Sign up to set email alerts
|

Depside Bond Formation by the Starter-Unit Acyltransferase Domain of a Fungal Polyketide Synthase

Abstract: Depsides are polyphenolic molecules comprising two or more phenolic acid derivatives linked by an ester bond, which is called a depside bond in these molecules. Despite more than a century of intensive research on depsides, the biosynthetic mechanism of depside bond formation remains unclear. In this study, we discovered a polyketide synthase, DrcA, from the fungus Aspergillus duricaulis CBS 481.65 and found that DrcA synthesizes CJ-20,557 (1), a heterodimeric depside composed of 3-methylorsellinic acid and 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…63,64 Thus, in the aligned assembly of AKR and ADH in the -X-Y-X-Ymanner alignment impedes diffusion of the intermediates into the bulk solution 65,66 and reduces the transient time, 10 resulting in a higher reaction rate through substrate chanelling. 46,67 This is analogous to that observed in enzymatic cascades in vivo, such as the natural polyketide synthase module, 68,69 In addition, intensified artificial vectorial catalysis in the close alignment of AKR and ADH can also cause macromolecular crowding 70,71 and induce conformational changes that directly affect the structure of active sites in favour of increasing affinity for substrates. 72 In these crowded environments the conformational flexibility of enzymes and protein dynamics critical to enzyme catalysis 73 can be altered.…”
Section: Enzymatic Enantioselective Synthesis Of the Chiral Alcohol U...mentioning
confidence: 70%
“…63,64 Thus, in the aligned assembly of AKR and ADH in the -X-Y-X-Ymanner alignment impedes diffusion of the intermediates into the bulk solution 65,66 and reduces the transient time, 10 resulting in a higher reaction rate through substrate chanelling. 46,67 This is analogous to that observed in enzymatic cascades in vivo, such as the natural polyketide synthase module, 68,69 In addition, intensified artificial vectorial catalysis in the close alignment of AKR and ADH can also cause macromolecular crowding 70,71 and induce conformational changes that directly affect the structure of active sites in favour of increasing affinity for substrates. 72 In these crowded environments the conformational flexibility of enzymes and protein dynamics critical to enzyme catalysis 73 can be altered.…”
Section: Enzymatic Enantioselective Synthesis Of the Chiral Alcohol U...mentioning
confidence: 70%
“…The remaining genes in the moll BGC encode a transcription factor (mollA), a flavinbinding oxidoreductase (mollB), a decarboxylase (mollC), a cytochrome P450 monooxygenase (mollD), and an aromatic prenyltransferase (mollF) (Table S1). Further phylogenetic analysis reveals that MollE is most homologous to DrcA, 15 Atr1, 13 Preu6, 16 and DepH 17 (Figure S3), a group of NR-PKSs that were recently reported for the biosynthesis of depsides. A homologous cytochrome P450 monooxygenase of DepG has been identified to catalyze the ether formation in the biosynthesis of the depsidone nornidulin.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…A biosynthetic gene cluster (BGC) containing a nonreducing polyketide synthase (NR-PKS) CgrPKS16 and a cytochrome P450 monooxygenase from a lichen-associated fungus Cladonia grayi has been proposed for the biosynthesis of the depsidone grayanic acid by transcription analysis . Heterologous expression studies demonstrated that a single NR-PKS is responsible for catalyzing the formation of the aromatic subunits and the subsequent esterification reaction to generate the depsides atranorin and lecanoric acid in the lichens Stereocaulon alpinum and Pseudevernia furfuracea , respectively. , Remarkably, the esterification reaction to form the depside CJ-20577 was biochemically confirmed to be catalyzed by the starter acyl transferase (SAT) domain of the NR-PKS DrcA, and ester bond formation in lecanoric acid was catalyzed by the interaction of SAT and the thioesterase (TE) domain of the NR-PKS Preu6 (Figure S1). Recently, after releasing the depside from the TE domain of NR-PKS DepH, a dedicated cytochrome P450 DepG was identified to generate an ether bond to form the depsidone (Figure B and Figure S1).…”
mentioning
confidence: 99%
“…To investigate whether the str cluster is responsible for the biosynthesis of an alkyl salicylaldehyde derivative, we performed heterologous expression experiments using Aspergillus oryzae NSAR1, which has been utilized for the characterization of orphan biosynthetic gene clusters . First, the PKS gene strA was solely expressed in A.…”
Section: Results and Discussionmentioning
confidence: 99%